2010
DOI: 10.1007/s00268-010-0891-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Prognostic Factors Related to Overall Survival in Patients with Stage IV Colorectal Cancer and Unresectable Metastases

Abstract: Each patient should be reviewed individually on the basis of the above independent prognostic factors before deciding to resect the primary tumour. Patients with a poor performance status, extensive hepatic metastases, and extensive nodal disease detected preoperatively are less likely to have a survival benefit. Nonsurgical approaches to manage these patients should be given careful consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 63 publications
2
50
0
1
Order By: Relevance
“…Several new biomolecular markers have been proposed: EGFR gene copy number, NRAS, PIK3CA mutations, loss of PTEN expression, the presence of Insulin-like growth factor 2 messenger RNA binding protein 3 in cancer cells [11][12][13][14] The determination of these factors is costly and some of them are experimental and then reserved to specialized centers. Moreover, all these markers are not timedependent, and thus they could not reflect a change in tumor biology over time.…”
Section: Discussionmentioning
confidence: 99%
“…Several new biomolecular markers have been proposed: EGFR gene copy number, NRAS, PIK3CA mutations, loss of PTEN expression, the presence of Insulin-like growth factor 2 messenger RNA binding protein 3 in cancer cells [11][12][13][14] The determination of these factors is costly and some of them are experimental and then reserved to specialized centers. Moreover, all these markers are not timedependent, and thus they could not reflect a change in tumor biology over time.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with four or fewer isolated hepatic lesions, five year relapse-free survival rates range from 24 to 58 percent and ten year survival rates vary between 17 and 33 percent. There is a convincing socio-epidemiological evidence of the dramatic unfavourable influence on population wealth of untimely diagnosis and inadequate treatment of the patients with advanced and metastatic colorectal cancer worldwide (Hata et al, 2010;Kostov & Kobakov, 2006a;Stillwell et al, 2011;Tsoulfas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Due to poor sensitivity, its therapeutic effect of single application is not significant, so it is frequently used in combination with other tumor markers. Elevated CEA demonstrated that the metastasis occurred in tumor or the tumor is at an advanced stage (Stillwell et al, 2011). In 1976, the study made by Herrer, et al had revealed the staging effect of CEA on colon cancer, namely preoperative elevated CEA level suggests the tumor is at an advanced stage (Herrere et al, 1979).…”
Section: Discussionmentioning
confidence: 99%